Characteristics and Outcomes of Community Acquired Versus Hospital Acquired Sepsis at A Tertiary Care Hospital, Karachi - Rabeea Shah, Naseem Salahuddin, Shameem Behram Khan, Rabiah Masroor, Kiran Abbas, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The study compared the demographics, clinical characteristics and site of infection leading to community acquired and hospital acquired sepsis. Secondly, the study further compared the distribution of the isolated organisms and complications caused by community and hospital acquired sepsis. Methods: A prospective cohort study was undertaken at the intensive care unit, high dependency unit, and critical care unit at the Indus Hospital, Karachi, Pakistan between 14-April-2021 to 15th-April-2022. All the individuals diagnosed with sepsis, admitted through the Emergency Department or transferred from a ward were included in the study. Age < 15 years or who were shifted from another hospital were removed from the study. The data on demographics, vital signs, SOFA score, site of infection, laboratory parameters, radiological investigations, culture results, and complications, if any, were filled on a pre- designed Performa. Results: Age of the participants was 42.1 ± 17.4 years with a predominance towards female gender. Urinary tract was the most common site from which the organisms were isolated with a frequency of 35 (28.9%). Table 3 revealed that gender was significantly associated with gender (p=0.008). It was found that the majority of the community acquired sepsis were reported in males while the majority of the hospital acquired sepsis was reported in females. Furthermore, marital status (p=0.019) and site of infection were significantly correlated with the hospital acquired sepsis. It was further found that mean creatinine was significantly lower in community acquired sepsis than those with hospital acquired sepsis [(7.83 ± 4.85) vs (15.4 ± 10.4); p<0.001]. Conclusion: The study revealed both hospital acquired and community acquired sepsis are life threatening conditions that may add significant burden on the healthcare facility while at the same time placing significant financial burden upon the patients. Keywords: Sepsis; Community-acquired infections; Nosocomial; Mortality